2005
DOI: 10.1101/gr.4100405
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation of genes and repeats in land plants

Abstract: The hypomethylated fraction of plant genomes is usually enriched in genes and can be selectively cloned using methylation filtration (MF). Therefore, MF has been used as a gene enrichment technology in sorghum and maize, where gene enrichment was proportional to genome size. Here we apply MF to a broad variety of plant species spanning a wide range of genome sizes. Differential methylation of genic and non-genic sequences was observed in all species tested, from non-vascular to vascular plants, but in some cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
3
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 104 publications
(112 reference statements)
10
117
3
3
Order By: Relevance
“…The results indicate that Jinling elements are highly methylated at both of the CNG and CG sites (Figure 6). DNA methylation is often associated with reduced gene expression and previous studies in maize and Arabidopsis have also shown that repetitive sequences in heterochromatin are highly methylated (Bennetzen et al 1994;Lippman et al 2004;Rabinowicz et al 2005). A blastn search against .180,000 tomato ESTs (www.sgn.cornell.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that Jinling elements are highly methylated at both of the CNG and CG sites (Figure 6). DNA methylation is often associated with reduced gene expression and previous studies in maize and Arabidopsis have also shown that repetitive sequences in heterochromatin are highly methylated (Bennetzen et al 1994;Lippman et al 2004;Rabinowicz et al 2005). A blastn search against .180,000 tomato ESTs (www.sgn.cornell.…”
Section: Resultsmentioning
confidence: 99%
“…In higher plants, methylation of cytosines is present in CG, CHG (where H is A, C, or T), and asymmetric CHH sequence contexts (Henderson and Jacobsen, 2007). Recent studies have shown that cytosines are methylated not only in plant repetitive sequences and transposable elements (TEs) but also in promoters and gene bodies and that DNA methylation is highly correlated with transcription (Rabinowicz et al, 2005;Zhang et al, 2006;Vaughn et al, 2007;Zilberman et al, 2007;Cokus et al, 2008;Li et al, 2008c;Lister et al, 2008). Epigenetic changes, such as DNA methylation and histone modifications, do not act in isolation but rather in concert with each other, allowing for complex interdependencies.…”
Section: Introductionmentioning
confidence: 99%
“…Examples for several genes related to fiber development are provided. Given that the total number of genes in the cotton genome may be 50,000 (Rabinowicz et al 2005), the 1484 gene pairs tested here include perhaps 5% of the total genic diversity. This suggests that for every 5 genes suggested as candidates for novel gene recruitment, another 95 exist that were not explored.…”
mentioning
confidence: 99%